FACTORS INFLUENCING MOTIVATION OF STAFF IN THE TR ANSPORT INDUSTRY IN KENYA: A CASE OF SIGINON FREIGHT LIMITED - MUNGA, MARTIN MWANGOME; SABABU, PROF. BONFACE M. (International Journal of Economics, 2016)
Purpose: The main objective of the study was to investigate factors influencing motivation of staff in transport industry. Methodology: The population of the study comprised of the employees of Siginon who worked in the transport and logistics section. Stratified random sampling was done on the employees who were stratified into three strata of senior management, middle management and officers. The respondents were finally identified using simple random sampling. The feedback obtained from the questionnaires was used to gather the data needed for this study. Information was sorted, coded and input into the statistical package for social sciences (SPSS). Data was analyzed by use of descriptive and inferential statistics. SPSS version 17 was used to run the statistical tests on the data. Descriptive statistics included the use of percentages and mean. Inferential statistical tests were also done to derive correlation and regression coefficients. Data was presented in forms tables. The analysis included frequencies, descriptive and inferential statistics. Results: Study results revealed that employees of Signon were motivated by salary, pension, bonus and contingent pay. Based on the results and findings it was concluded that despite the short and quick effect on motivation, bonus could be used to direct the energies of employees towards to desire company targets. Unique contribution to theory, practice and policy: It is recommended to the management of Siginon to regularly conduct salary reviews with an objective of ensure equity and justice in pay with an overall objective of inducing motivation in employees. It is recommended to the management that they review the existing social security benefits including pension benefits with a targeted aim of improving employee motivation. A case in point is the elimination of all forms of discrimination in providing pension benefits. Another study could be carried out to include other potential drivers of motivation like; working conditions, employee transport, medical cover, company image and management style.